Effect of breathing exercises combined with behavioral intervention in nursing of patients with asthma (呼吸训练联合行为干预在哮喘患者护理中的应用效果观察) - TIAN Shuijing (田水静); ZHANG Wenzheng (张文峥); WANG Yan (王燕) (中西医结合护理)
Objective To investigate the effect of breathing exercises combined with behavioral intervention in nursing of patients with asthma patients, and provide reference for the nursing quality improvement. Methods Totally 90 cases of asthma patients admitted to the hospital from May 2021 to February 2023 were selected and divided into a control group and an observation group using a randomized numerical table method, with 45 cases in each group. The control group received routine care, and the observation group was given breathing exercises and behavioral interventions on the basis of the control group. Score of quality of life assessment, duration of oxygen intake, nursing effectiveness and nursing satisfaction were observed in both groups. Results The score of quality of life assessment was increased in both groups after intervention, and score of quality of life assessment in the observation group was higher than that in the control group (P＜0. 01). The total duration of oxygen intake in the observation group was lower than that in the control group. The total effective rate of nursing and nursing satisfaction of patients in the observation group were higher than those of the control group (P＜0. 05). Conclusion In addition to routine care, breathing exercises and behavioral interventions may improve patients' quality of life, reduce the duration of oxygen intake, increase the nursing efficiency, and is conductive asthma control. (目的 探究呼吸训练联合行为干预在哮喘患者护理中的应用效果, 为提升哮喘护理质量提供参考。方法 选取2021年5月—2023年2月医院收治的90例哮喘患者为研究对象, 采用随机数字表法分为对照组和观察组, 每组45例。对照组施加常规护理, 观察组在对照组基础上实施呼吸训练及行为干预。对比两组患者的生活质量评分、吸氧时长、护理有效率和护理满意度。结果 干预后, 两组患者生活质量评分均较干预前提高, 且观察组评分高于对照组(P＜0. 01)。观察组总吸氧时长短于对照组。观察组护理总有效率和护理满意度均高于对照组, 差异有统计学意义(P＜0. 05)。结论 将呼吸训练及行为干预引入常规护理中, 能够提高患者生活质量, 降低吸氧时长, 提升护理效率, 有利于哮喘病情控制。)